2022
DOI: 10.1139/cjc-2022-0062
|View full text |Cite
|
Sign up to set email alerts
|

VUV photoprocessing of oxygen-containing polycyclic aromatic hydrocarbons: iPEPICO study of the unimolecular dissociation of ionized benzofuran

Abstract: Oxygen-containing polycyclic aromatic hydrocarbons (OPAHs) are potential contributors to the 11.3 m band in interstellar observations. To further explore their role in the interstellar medium, we have investigated their fate after photoprocessing by VUV radiation; in particular, we studied the dissociative photoionization of the simplest OPAH, benzofuran, with imaging photoelectron photoion coincidence spectroscopy, iPEPICO. Ionized benzofuran dissociates by loss of CO, followed by a sequential H atom loss. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…This is followed by further fragmentation into one of the three additional channels via either loss of an additional CO, COH n , or C 2 H 4±n resulting in the (257 ± 2) amu channel or breaking apart resulting in two fragments that are similar in size, for example the smaller two-carbon ring aromatics naphthalene (128 amu) and naphtaldehyde, ethylnaphthalene, or dimethylnaphthalene (all three species have a mass of 156 amu). These results are consistent with imaging photoelectron photoion coincidence (iPEPICO) spectroscopy experiments investigating the dissociative photoionization of the OPAH benzofuran (Zinck et al 2022) and of hydroxy-substituted PAH cations (Lesniak et al 2019) that revealed their primary dissociation channel to be CO-and HCO-loss.…”
Section: Daughter-mass Spectrometrysupporting
confidence: 86%
“…This is followed by further fragmentation into one of the three additional channels via either loss of an additional CO, COH n , or C 2 H 4±n resulting in the (257 ± 2) amu channel or breaking apart resulting in two fragments that are similar in size, for example the smaller two-carbon ring aromatics naphthalene (128 amu) and naphtaldehyde, ethylnaphthalene, or dimethylnaphthalene (all three species have a mass of 156 amu). These results are consistent with imaging photoelectron photoion coincidence (iPEPICO) spectroscopy experiments investigating the dissociative photoionization of the OPAH benzofuran (Zinck et al 2022) and of hydroxy-substituted PAH cations (Lesniak et al 2019) that revealed their primary dissociation channel to be CO-and HCO-loss.…”
Section: Daughter-mass Spectrometrysupporting
confidence: 86%
“…On the other hand, one of the CH 2 hydrogens in the five-membered ring in [ 46 ] may transfer to the OH group over the transition state [ 48 ] ‡ at a barrier of 1.97 eV, which leads to water loss and the m / z 118 fragment ion benzofuran [ 49 ]. As evidenced by their similar ionization energy but lower DPI onset, , oxygen-containing polycyclic aromatic hydrocarbon cations are less stable than the hydrocarbon analogues, which would be indene in this case. Therefore and despite the large kinetic energy release upon water loss on account of the 2.06 eV reverse barrier, [ 49 ] is a likely intermediate on the way to the m / z 90 fragment ion by consecutive CO loss at higher photon energies in ortho -anisaldehyde DPI.…”
Section: Resultsmentioning
confidence: 80%
“…The transition state [54] ‡ energy is calculated to be lower than that of the intermediate state [53], which shows a slight disagreement between the density functional theory geometry optimization and the wave function theory energies in the G4 composite method. 49 At the same time, it also indicates a flat reaction energy curve, which may act as a bottleneck and, together with quantum tunneling across the [48] ‡ barrier with a 1373 cm −1 critical frequency, may explain the dominance of the m/z 118 fragment ion in the BD (Figure 3c), while the m/ z 94 channel stays relatively minor.…”
Section: Dissociative Ionization Mechanism Of Ortho-anisaldehydementioning
confidence: 90%
See 2 more Smart Citations